Donor leucocyte infusion - Sousa, Adriana Martins de; Tavares, Rita de Cassia Barbosa; Santis, Gil Cunha De; Seber, Adriana (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2026)
Donor-derived cellular therapies play a pivotal role in optimizing outcomes after allogeneic hematopoietic stem-cell transplantation (HCT). This article reviews three key post-transplant interventions: donor lymphocyte infusion (DLI), hematopoietic stem-cell boost, and mesenchymal stromal cell (MSC) infusion. DLI remains a cornerstone strategy for enhancing graft-versus-leukemia effects, preventing or treating relapse, and promoting immune reconstitution, while also carrying risk of graft-versus-host disease. Stem-cell boosts, typically performed using CD34⁺ selected products, offer an effective approach for managing poor graft function or mixed chimerism without significantly increasing alloimmune toxicity. MSC infusion has emerged as a promising immunomodulatory therapy for steroidrefractory graft-versus-host disease and for facilitating engraftment, owing to its anti-inflammatory and tissueregenerative properties.